Knowledge on involvement during pregnancy among fathers in respective areas in Kuantan, Malaysia - Mohd Hanapi, Nurul Nabilah; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (Elsevier, 2019)
Objective: This study aims to identify the knowledge on the involvement of father during pregnancy among fathers in the respective area in Kuantan. Method: The study was conducted as a cross-sectional with a quantitative study. There were 103 participants recruited. The data of this study were analyzed by using Statistical Package for Social Science (SPSS) with one-way ANOVA and Pearson correlation test for significant analyses. Result: The result showed that half of the fathers have high knowledge of pregnancy and knowledge on involvement regarding pregnancy. There is a significant difference between age factors with mean knowledge of father regarding pregnancy. Meanwhile, there is also a significant difference between age and knowledge on the involvement of father during pregnancy. In addition, a number of children and knowledge on the involvement of father during pregnancy also showed a significant association. The knowledge level of father regarding pregnancy and the knowledge on involvement during pregnancy among fathers is directly, linearly and moderately correlated. Conclusion: This study can be concluded that fathers in Kuantan are possessed average knowledge on involvement regarding pregnancy. This shows that man lag behind in their responsibilities in pregnancy. In which, they do not clearly know what their role is during pregnancy